The Case for an Independent Fiscal Institution in Japan - Kopits, George (IMF Working Papers; Working Paper ;, 2016)
In response to the recent financial crisis and the ensuing buildup in public indebtedness, an increasing number of advanced economies have created independent fiscal institutions (IFIs) to improve the quality of public finances and to strengthen the credibility of government policy. A review of Japan's fiscal policymaking over the past decades suggests that Japan would greatly benefit from establishing an IFI in line with internationally accepted standards of good practice. Such an institution could help correct critical weaknesses in policymaking and anchor expectations, especially if introduced as part of a fiscal framework with a medium-term perspective.